Electrocoagulation Method to Reduce Pollutants in the Wastewater of Jumputan Fabric Industry - Rusdianasari Rusdianasari; Ibnu Hajar; Indri Ariyanti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
The existence of the textile industry in Indonesia is not only in the category of large and medium scale industries but also in small scale and some even in the home industry. These caused pollution mainly as a result of the dyeing of textiles. Dye not only occurs in industrial areas but also occurs in densely populated settlements. An attempt to treat the waste of the textile industry is needed to solve the environmental pollution. In this research, liquid waste was processed using the electrocoagulation method, and the expected concentration or hazard caused by waste was decreased and to fulfill the required environmental quality standard. Treatment of jumputan wastewater by electrocoagulation method using 4 aluminum electrodes 11x10.5 cm in size with MP-P configuration type (Monopolar-Paralel) for 120 minutes. The parameters measured in this study were chromium heavy metal content, TSS (Total Suspended Solid), TDS (Total Dissolved Solids), as well as changes in pH, color and turbidity values where the applied voltage variations were 10, 13, 15, 17, and 20 volts with variation of electrode distance used 1.5; 2.0; and 2.5 cm. The best condition for each parameter was obtained at a distance of 1.5 cm with a voltage of 20 volts. Effectiveness of electrocoagulation method to decrease turbidity value up to 99.84%; color 99.33%, chromium content of 62.5%; TSS 33.68%; TDS of 66.59% and raised the pH from 5.64 to 8.10, respectively.